Synthesis and characterization of PCL-PEG-PCL 5000-1000-500 tri block copolymer (Asian Journal of Pharmaceutics (AJP), 2024)
Objective: The objective of this study was to synthesize novel, amphiphilic, triblock, biodegradablepolycaprolactone-polyethylene glycol-polycaprolactone (PCL-PEG-PCL) (5000–1000–1000) copolymer throughring-opening polymerization of ε-caprolactone (CL) using PEG as an initiator for long-acting drug delivery andbiomedical applications. Materials and Methods: The copolymers were synthesized through ring-openingpolymerization of ε-CL using stannous octoate as the catalyst. The resulting copolymers were characterizedby 1H nuclear magnetic resonance spectroscopy (NMR), 13C NMR spectroscopy to determine the compositionand end group estimation, gas chromatography (GC) for residual solvent estimation, fourier-transform infraredspectroscopy (FTIR) for identification of functional groups, X-ray diffraction, thermogravimetric analysis, anddifferential scanning calorimetry to analyze the thermal properties. Results and Discussion: 1H NMR spectrarevealed ethylene groups at 1.35, 1.69, 2.43, and 4.06 ppm in PCL, while PEG displayed methylene (CH2) groupsat 3.8 ppm. In addition, the FTIR spectra of the PCL-PEG-PCL copolymer exhibited prominent bands at 1720cm-1,indicative of carboxylic ester, C=O and 1175cm-1, indicative of ether, C-O, confirming the successful synthesisof the copolymer. PEG triblock polymer end cap analysis and molar ratio of CL:PEG for synthesized triblockcopolymer was found to be hydroxyl end cap and 91:09, respectively. The GC results of triblock polymer werefree of dichloromethane and water content was 0.2%. The copolymer exhibited distinct peaks at diffraction angles(2θ) of 21.14°, 23.45°, 20.14°, 35.8°, and 12.15°. It demonstrates that the copolymer was presented in crystallineform. Conclusion: Based on the data obtained, concluded that the synthesized triblock copolymer provided anacceptable and appropriate novel polymer for long-acting drug delivery and various biomedical applications.